In vitro and in vivo Virulence Potential of the Emergent Species of the Acinetobacter baumannii (Ab) Group - Cosgaya, Clara; Ratia, Carlos; Marí-Almirall, Marta; Rubio, Laia; Higgins, Paul G.; Seifert, Harald; Roca, Ignasi; Vila, Jordi (Frontiers in Microbiology, 2019)
The increased use of molecular identification methods and mass spectrometry has revealed that Acinetobacter spp. of the A. baumannii (Ab) group other than A. baumannii are increasingly being recovered from human samples and may pose a health challenge if neglected. In this study 76 isolates of 5 species within the Ab group (A. baumannii n=16, A. lactucae n=12, A. nosocomialis n=16, A. pittii n=20, and A. seifertii n=12), were compared in terms of antimicrobial susceptibility, carriage of intrinsic resistance genes, biofilm formation, and the ability to kill Caenorhabditis elegans in an infection assay. In agreement with previous studies, antimicrobial resistance was common among A. baumannii while all other species were generally more susceptible. Carriage of genes encoding different efflux pumps was frequent in all species and the presence of intrinsic class D β-lactamases was reported in A. baumannii, A. lactucae (heterotypic synonym of A. dijkshoorniae) and A. pittii but not in A. nosocomialis and A. seifertii. A. baumannii and A. nosocomialis presented weaker pathogenicity in our in vitro and in vivo models than A. seifertii, A. pittii and, especially, A. lactucae. Isolates from the former species showed decreased biofilm formation and required a longer time to kill C. elegans nematodes. These results suggest relevant differences in terms of antibiotic susceptibility patterns among the members of the Ab group as well as highlight a higher pathogenicity potential for the emerging species of the group in this particular model. Nevertheless, the impact of such potential in the human host still remains to be determined.